From reluctant slavery to a black flood: Black workers, mass production and cultural formation in South Africa's metalworks - Sitas, A. (My University, 1982)
In the first chapter of this thesis the problem of the transition from absolute to relative surplus-value extraction, of the changes in the social relations of production that bring about the mass production of commodities in South Africa's Metalworks, was discussed in some detail. There it was shown that South Africa's bonded accumulation and reproduction of capital, militated against such a transition: The local Metalworks, subordinate on the one hand to an international division of labour, on the other, to the needs of the local mining industry, faltered in all their efforts to effect this transition. Furthermore, through a discussion of the economic role of the South African State it was emphasised that the first pockets of mass producing Metalworks, like Iscor and the African Metals Corporation were created through State or para-statal corporations. This entailed a vast reorganisation of the industry by the late 19 30s. Finally, despite the favourable conditions for growth engendered by the Union's 'war effort', the dominance of these new relations of production was shown to be tenuous and a continued juxtaposition of jobbing and mass forms of production defined the morphology of the industry by the 1950s. The second chapter of the thesis addressed itself to the transition itself, located in the era after 1964 and consolidated by the crisis years of the mid-nineteen-seventies. Primarily through a rapid concentration and centralisation of the industry but also through the sudden large scale involvement of Mining Houses and Transnational Corporations, the 'universal worker' of machinofacture is created. The absolute increase of operative African workers turn from a quantitative flood to a qualitative presence. This present chapter is an attempt to examine the contradictory implications of this presence, in the words of the author M. Dikobe a generation 'that is surprising the world, fast very fast', in its combativity and political consciousness (1).
African Studies Seminar series. Paper presented 2 August 1982
Keywords: Metal-workers. South Africa; Blacks. Employment. South Africa